Fuzzy Neural Network Technology Support Decision-Making; Advances in Computer Science Research; Vol. 72 : Information technologies in Science, Management, Social sphere and Medicine (ITSMSSM 2017) - Nguyen Anh Tu (2017, 2017)
Title screen